The Role of Planning Management in Implementing Digital Transformation to Improve Operational Efficiency in Nickel Manufacturing Companies - Setiawan, Yoga; Santoso, Wiliam (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to examine the role of planning management in implementing digital transformation to improve operational efficiency in nickel manufacturing companies. Grounded in Dynamic Capabilities Theory, this research investigates both the direct effects and the mediating roles of management planning, digital transformation, and operational efficiency. A quantitative approach using PLS-SEM analysis is employed to test five hypotheses, with a particular focus on the role of dynamic capabilities. The literature review indicates that dynamic capabilities play a crucial role as a linkage between planning management and digital transformation, thereby enhancing operational efficiency. This study highlights the importance of management strategy in adapting to the Industry 4.0 era in order to maintain competitiveness and ensure corporate sustainability amid a highly uncertain global environment.